FAKTOR DETERMINAN PENGAMBILAN KEPUTUSAN MENJADI MUSLIMPRENEUR ( STUDI PADA ANGGOTA IIBF KOTA BANDUNG ) - Noviandra Gunawan, - (2020)
Decision-making is an important final process for someone to make a choice, including being a Muslimpreneur. Many internal and external factors influence this decision. Interest and level of religiosity is one of the factors that influence this decision. This study is to analyze the extent to which the interest factor and the level of religiosity influence the decision making to become a Muslimpreneur. The method used in this research is causality with a quantitative approach. The population in this study are members of the Indonesian Islamic Business Forum Bandung City. The sampling technique used was probability sampling with the type of sampling used was simple random sampling of 236 respondents. The data analysis technique used is Patrial Least Square - Structural Equation Modeling (PLS-SEM). The results showed that interest and level of religiosity had a positive and significant effect on the decision-making to become a Muslimpreneur. This research is expected to provide benefits to various parties, especially Muslim entrepreneurial organizations and also the government to further enhance their capabilities in fostering a competent entrepreneurial spirit so that prosperity in Indonesia can be achieved.